Economic, Environmental, and Social Assessment of Concrete Pavement Life Cycle: A Literature Review - Mohammad saleh Entezari; Rashid Tanzadeh; Fereidoon Moghadas Nejad (مهندسی عمران شریف)
Concrete is extensively utilized in road pavement construction, including continuously reinforced, jointed plain, jointed reinforced, precast, and eco-block concrete pavements. However, the pavement industry faces significant challenges, such as high construction and maintenance costs, substantial energy consumption, pollution emissions during material production, and adverse impacts of work zones on workers and communities. These multifaceted impacts are evaluated through economic, environmental, and social life-cycle assessment (LCA) tools, forming the basis of life-cycle sustainability assessment (LCSA). This article reviews the historical development of LCSA and outlines its methodological steps based on existing standards. A critical review of concrete pavement LCSA studies examines their scope, including analysis pillars, life-cycle stages, unit processes, pavement types, tools, life-cycle inventory (LCI), and impact categories. Key gaps are identified: only 25% of studies address the use phase, while a mere 20% consider the end-of-life stage. Within the use phase, common focuses include roughness-induced fuel consumption (10% of studies), vehicle operation costs (10%), and work zone impacts (traffic delays: 15%; increased fuel consumption: 10%). Notably, pavement albedo, carbonation, and lighting effects were analyzed in only one study, while CO₂ was the most frequent LCI item (11 references). To address these limitations, the study proposes a standardized framework for scope definition in concrete pavement LCSA, ensuring comprehensive inclusion of unit processes across all life-cycle stages to enhance result reliability. The article concludes with recommendations for future research to advance LCSA methodologies.